Pelvic Belt Effects on Health Outcomes and Functional Parameters of Patients with Sacroiliac Joint Pain. - Niels Hammer; Robert Möbius; Stefan Schleifenbaum; Karl-Heinz Hammer; Stefan Klima; Justin S Lange; Odette Soisson; Dirk Winkler; Thomas L Milani (PLoS ONE, 2015)
The sacroiliac joint (SIJ) is a common source of low back pain. However, clinical and functional signs and symptoms correlating with SIJ pain are widely unknown. Pelvic belts are routinely applied to treat SIJ pain but without sound evidence of their pain-relieving effects. This case-control study compares clinical and functional data of SIJ patients and healthy control subjects and evaluates belt effects on SIJ pain.17 SIJ patients and 17 healthy controls were included in this prospective study. The short-form 36 survey and the numerical rating scale were used to characterize health-related quality of life in patients in a six-week follow-up and the pain-reducing effects of pelvic belts. Electromyography data were obtained from the gluteus maximus, biceps femoris, rectus femoris and medial vastus. Alterations of muscle activity, variability and gait patterns were compared in patients and controls along with the belts' effects in a dynamic setting when walking.Significant improvements were observed in the short-form 36 survey of the SIJ patients, especially in the physical health subscores. Minor declines were also observed in the numerical rating scale on pain. Belt-related changes of muscle activity and variability were similar in patients and controls with one exception: the rectus femoris activity decreased significantly in patients with belt application when walking. Further belt effects include improved cadence and gait velocity in patients and controls.Pelvic belts improve health-related quality of life and are potentially attributed to decreased SIJ-related pain. Belt effects include decreased rectus femoris activity in patients and improved postural steadiness during locomotion. Pelvic belts may therefore be considered as a cost-effective and low-risk treatment of SIJ pain.ClinicalTrials.gov NCT02027038.